Significance of CD34 Negative Hematopoietic Stem Cells and CD34 Positive Mesenchymal Stem Cells – A Valuable Dimension to the Current Understanding - Viswanathan, Chandra; Kulkarni, Rohit; Bopardikar, Abhijit; Ramdasi, Sushilkumar (Current Stem Cell Research & Therapy, 2017)
Background: The strategy to expand CD34+ hematopoietic stem cells (HSCs) is being increasingly practiced to meet the demand for a higher cell dose. This is for hematopoietic reconstitution in patients with higher body weights. Interestingly, literature reports show that CD34- (CD34 negative) cell population also possesses the potential to reconstitute the bone marrow & in a certain phase, converts them into CD34+ phenotype. The current practice of positive selection of CD34+ HSCs by eliminating rest of the (CD34-) population for expansion could probably pose a risk of losing valuable HSCs with good reconstitution potentials. MSCs (Mesenchymal Stem Cells) hold great promise for use in various regenerative medicine applications. International Society for Cellular Therapy (ISCT) defined MSCs to be CD34 negative; tissue resident MSCs and peripheral blood-derived MSCs express CD34 on their surface even in vitro, though up to limited passages. This interesting observation of CD34 positive expression displayed in vivo by non-hematopoietic cell types such as MSCs was intriguing, thus prompting a detailed review of its significance, if any. Objective: Based on an extensive review, we strongly believe that CD34 expression in MSCs has some significant role in hematopoietic reconstitution & in regeneration of degenerated tissues. The concept of poor CD34 expression or stunted expression by certain MSCs should not be ignored. Several interesting research findings are in agreement with our assumption. However, it still leaves behind several unanswered questions that can only be addressed through detailed studies of phenotypic developmental pathways of MSCs.
Keywords: bone marrow